The Propagation Technology Of A Unique Orchid Flower In Namangan's Environmental Conditions. (Texas Journal of Agriculture and Biological Sciences, 2024)
The unique orchid flower is said to be unique in that there are more than 25,000 species in the world, and many species are now endangered, and the reproduction process of this flower is much more difficult than other flowers. One orchid seed can grow from 1300 to 4000000 seeds, which makes the plant the leader among flowers in terms of seed yield, but it is much more difficult to fertilize this flower and seeds. Orchid and mushroom live in symbiosis, because they also have important conditions for germination or if there is a root coexisting fungal environment.